A pediatric institutional acute stroke protocol improves timely access to stroke treatment. (4th August 2016) - Shack, Melissa; Andrade, Andrea; Shah‐Basak, Priyanka P; Shroff, Manohar; Moharir, Mahendranath; Yau, Ivanna; Askalan, Rand; MacGregor, Daune; Rafay, Mubeen F; deVeber, Gabrielle A
Abstract : Aim: We aimed to evaluate whether an institutional acute stroke protocol (ASP) could accelerate the diagnosis and secondary treatment of pediatric stroke. Method: We initiated an ASP in 2005. We compared 209 children (125 males, 84 females; median age 4.8y, interquartile range [IQR] 1.2–9.3y, range 0.09–17.7y) diagnosed with arterial ischemic stroke 'pre‐protocol' (1992–2004) to 112 children (60 males, 52 females; median age 5.8y, IQR 1.0–11.4y, range 0.08–17.7y) diagnosed 'post‐protocol' (2005–2012) for time‐to‐diagnosis, mode of diagnostic imaging, and time‐to‐treatment with antithrombotic medication (aspirin or anticoagulants). Results: Overall, the interval from symptom onset to diagnosis was similar post‐protocol compared to pre‐protocol (20.3 vs 22.7h; p= 0.109), although mild strokes (Pediatric National Institute of Health Stroke Scale [PedNIHSS] 0–4), were diagnosed faster post‐protocol (12.1 vs 36.3h; p= 0.003). Magnetic resonance imaging (MRI) was the initial diagnostic modality more often post‐protocol (25% vs 1.4%; p <0.001). Initial MRI was more accurate for diagnosing stroke than initial CT (100% vs 47%; p <0.001) with similar time‐to‐diagnosis. The proportion of children receiving antithrombotic medication within 24 hours doubled in the post‐protocol period (83% vs 36%; p <0.001). Interpretation: A pediatric ASP accelerated time‐to‐treatment, time‐to‐diagnosis in children with subtle strokes, and increased MRI as initial imaging, reducing the need for computed tomography. Implementing optimized ASPs can facilitate more timely access to diagnosis and management of children with acute stroke. What this paper adds: After pediatric acute stroke protocol (ASP), 'MRI 1st and only test' can replace initial computed tomography without delaying diagnosis. After ASP, children receive antithrombotic treatment faster and more often. After ASP, mild strokes are diagnosed more quickly.